Beyond the natural flow regime? Broadening the hydro‐ecological foundation to meet environmental flows challenges in a non‐stationary world. (26th October 2017) - Poff, N. LeRoy
Abstract: The natural flow regime concept has contributed significantly to environmental flows (e‐flows) science and applications over the last 20 years. Natural flow regimes reflect long‐term, historical patterns of flow variability that have shaped riverine species' adaptations and continue to shape community and ecosystem structure and function. This scientific perspective, however, carries with it important assumptions about climatic and ecological stationarity in terms of "reference" conditions that provide a basis for comparing success or outcomes of e‐flow interventions. Non‐stationarity in climate and other environmental conditions (temperature, sediment, nutrients) and in ecological features (non‐native species spread) presents important challenges for environmental flows science. Reliance on the assumption of restoration to reference conditions for either hydrologic or ecological conditions is no longer tenable, and an expanded e‐flows science foundation is needed to meet several challenges facing future e‐flows implementations. Currently recognised limitations of e‐flows science contribute to the emergence of research frontiers that need further development. These are (1) shifting from static, regime‐based flow metrics to dynamic, time‐varying flow characterisations; (2) expanding the ecological metrics (and space–time scales) used in e‐flows from primary reliance on ecosystem states to include process (population) rates and species traits; (3) incorporating other "non‐flow" environmental features (e.g. temperature, sediment) to guide prioritisation of e‐flows applications with a likelihood of success; and (4) broadening the ecological foundation of e‐flows to incorporate more ecological theory that will contribute to a more predictive science. The natural flow regime perspective of managing for historical variability will remain important to understand ecological response to hydrologic alterations and to inform e‐flows management. However, under shifting hydro‐climatic and ecological conditions, a new imperative of managing for resilience is emerging, that is, identifying and prescribing e‐flows to sustain robust, persistent and socially valued ecological characteristics in a flexible and adaptive management framework.